Etika Lingkungan Biosentris dalam Al-Quran: Analisis Tafsir Pelestarian Lingkungan Hidup Karya Kementerian Agama - Zainul Mun'im (Lajnah Pentashihan Mushaf Al-Qur'an, 2022)
This article aims to discover the concept of environmental ethics in the book Tafsir Pelestarian Lingkungan Hidup compiled by the Team of Lajnah Pentashihan Al-Qur’an, Ministry of Religion of the Republic of Indonesia. The article is a qualitative research with descriptive-analytical method. This article uses the theory of environmental ethics developed by Sonny Keraf as the basis for the analysis. This study shows that the interpretation of Tim Lajnah Pentashihan Al-Qur’an on environmental issues in Tafsir Pelestarian Lingkungan Hidup tends to put the basis of life to include all elements of nature, both human and others. Conservation of mountains, seas, water, animals and plants cannot be ignored just for the human necessity only. In exploring nature, humans are bound by the ethics that have been stipulated in the Qur'an, including learning from every natural disaster, not being excessive and extravagant, and a healthy life style. This paper shows that the environmental ethics discussed in Tafsir Pelestarian Lingkungan Hidup is tend towards an intermediate environmental ethic that is biocentric, strikethrough a view that makes all elements in the natural ecosystem as the basis of life.